Childhood fussy/picky eating behaviours: a systematic review and synthesis of qualitative studies - Hazel Wolstenholme; Colette Kelly; Marita Hennessy; Caroline Heary (BMC, 2020)
Abstract Fussy/picky eating behaviours are common across childhood. Recent reviews of the fussy eating literature focus on quantitative research and do not adequately account for families' subjective experiences, perceptions and practices. This review aims to synthesise the increasing volume of qualitative work on fussy eating. A systematic search of relevant databases was carried out. Studies were included if they were qualitative, published since 2008, with a primary focus on families' experiences, perceptions and practices regarding fussy eating, food neophobia, or food refusal in children (aged one to young adult). Studies with clinical samples, or relating to children under one year were excluded. Ten studies were eligible for this review and were synthesised using meta-ethnography (developed by Noblit and Hare). This review provides a comprehensive description and definition of fussy eating behaviours. A conceptual model of the family experience of fussy eating was developed, illustrating relationships between child characteristics (including fussy eating behaviours), parent feeding beliefs, parent feeding practices, mealtime emotions and parent awareness of food preference development. Our synthesis identified two ways in which fussy eating relates to mealtime emotions (directly and via parent feeding practices) and three distinct categories of parent beliefs that relate to fussy eating (self-efficacy, attributions and beliefs about hunger regulation). The model proposes pathways which could be explored further in future qualitative and quantitative studies, and suggests that parent beliefs, emotions, and awareness should be targeted alongside parent feeding practices to increase effectiveness of interventions. The majority of studies included in this review focus on pre-school children and all report the parent perspective. Further research is required to understand the child's perspective, and experiences of fussy eating in later childhood. PROSPERO Registration: CRD42017055943